Modeling Root-Knot Nematode Regulation by the Biocontrol Fungus Pochonia chlamydosporia - Ciancio, Aurelio; Cabrera, Ileana Miranda; Hidalgo-Diáz, Leopoldo; Puertas, Ana; Duvergel, Yoannia Castillo (Frontiers in Fungal Biology, 2022)
Two models of increasing complexity were applied to simulate the interactions between the root-knot nematode (RKN) Meloidogyne incognita and the biocontrol fungus Pochonia chlamydosporia var. catenulata, in a rhizosphere microcosm. The models yielded discrete population dynamics at hourly rates, over a six months period and were validated using real parasitism and nematode or fungus observed densities. A general Pochonia-nematode-root model (GPNR) was based on five functions and sixteen biological constants. Variables and constants described the RKN life-cycle included the rates of: eggs production, hatching, juveniles (J2) and mature female development, root or nematodes self density-dependence factors. Other constants accounted for eggs parasitism, nematode-induced root losses, growth and mortalities. The relationship between nematodes and fungal propagules showed density dependence and cyclic variations in time, including an attractor on the propagules and J2 phases space. A second, more complex and detailed model (GPNRd), based on eight functions and 23 constants, was built as GPNR did not allow evaluation of host prevalence. It allowed simulations of all RKN life-stages and included non-parasitic and parasitic fungus population fractions. At given initial conditions, simulations showed a tendency towards stability in time, interpreted as effective host regulation. Both GPNR and GPNRd matched real J2 and fungus densities data, as observed in a RKN biocontrol assay. GPNRd showed a further density-independent nematode regulation mechanism, based on the P. chlamydosporia switch from a non-parasitic to a parasitic trophic behaviour. This mechanism supported the fungus biocontrol activity of M. incognita, which was sustained by a concomitant increase of roots density.